. The …first integral mehod for the Whitham-Broer-Kaup-Like equation with time dependent coefficient - Kılıç İnç Gençoğlu, B M M.t (My University, 2014)
The …first integral mehod for the Whitham-Broer-Kaup-Like equation with time dependent coefficient.
Bildiri - Yayımlanmamış
Bildiri - Kongre ve Sempozyum
Keywords: integral mehod the Whitham-Broer-Kaup-Like equation time dependent coefficient